2018
DOI: 10.1364/ao.57.001119
|View full text |Cite
|
Sign up to set email alerts
|

Highly amplified light transmission in a parity-time symmetric multilayered structure

Abstract: We propose a parity-time symmetric dielectric-nanofilm-dielectric multilayered structure that could facilitate highly amplified transmission of optical power in the infrared spectrum. We have theoretically studied our model using the transfer matrix formalism. The reflection and the transmission coefficients of the S-matrix are evaluated. The theoretical results are validated by FDTD numerical simulation. We have shown how the thickness of the layers and the gain/loss coefficient of the active layers could gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Following these theoretical suggestions, Rüter et al [4] have demonstrated the first experimental vindication of PT -symmetry in a configuration of linearly coupled waveguides. Since then, the study of PT -symmetry has been extended in diverse domains and phenomena, which include the onset of chaotic dynamics in optomechanical systems [5], modulational instability in complex media [6], soliton switch [7], active LRC circuits [8], optical oligomers [9][10][11][12][13][14][15][16], multilayered structures [17,18], unidirectional reflection-less transmission resonance in Bragg periodic structures [19,20], wireless power transfer [21], plasmonics [22,23] and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Following these theoretical suggestions, Rüter et al [4] have demonstrated the first experimental vindication of PT -symmetry in a configuration of linearly coupled waveguides. Since then, the study of PT -symmetry has been extended in diverse domains and phenomena, which include the onset of chaotic dynamics in optomechanical systems [5], modulational instability in complex media [6], soliton switch [7], active LRC circuits [8], optical oligomers [9][10][11][12][13][14][15][16], multilayered structures [17,18], unidirectional reflection-less transmission resonance in Bragg periodic structures [19,20], wireless power transfer [21], plasmonics [22,23] and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…In such a PT -symmetric optical waveguide configuration, the PT phase transition was characterized by a transition from periodically evolving optical power to exponential growth and decay of optical power in the two channels. In the context of optical systems, the notion of PT -symmetry has been explored in diverse domains such as optoelectronic oscillators [10], optomechanical systems [11][12][13], modulational instability in complex media [14], active LRC circuits [15], multilayered structures [16][17], unidirectional invisibility in periodic structures [18][19], wireless power transfer [20], optical lattices [21][22][23][24], double ring resonators [25], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…And in 2012, Rüter et al demonstrated the observation of PT -Symmetry in evanescently coupled waveguide structure with balanced gain and loss [25]. Since then, PT -Symmetry has been investigated in complex optical potentials [26], optomechanics [27][28], optical lattices [29], microring lasers [30], solitons [31][32][33], wireless power transfer [34], multilayered structures [35][36], many-body ultracold systems [37], Liénard oscillators [38] and so on.…”
mentioning
confidence: 99%